Impact Response Prediction Method of Packaging Systems with a Key Component considering Different Excitations and Cushioning Materials - Heye Xiao; ChiZhen Xu; Focai Yuan; Xudong Zhang; Junqiang Bai; Jie Zhou (Shock and Vibration)
Nonlinear dynamic models of the packaging systems that consider different excitations and cushioning materials are proposed to analyze their impact responses in this paper. To solve the nonlinear dynamic equations of the models, Newmark method is combined with Newton-Arithmetic mean method to transfer nonlinear equations to the linear discretization equations. Then, the acceleration responses and dropping damage boundary curves (DDBCs) of different nonlinear cushioning packaging systems are calculated conveniently with initial conditions. The good agreements between the simulated and tested results prove the accuracy and effectiveness of the proposed method. Furthermore, the effects of excitations parameters on the DDBCs of the packaging systems are analyzed. It is found that the key parameter for introducing differences between simulated and measured DDBCs is inappropriate duration configuration in the acceleration pulse test.